Who should decide for local health services? A mixed methods study of preferences for decision-making in the decentralized Philippine health system - Harvy Joy Liwanag; Kaspar Wyss (BMC, 2020)
Abstract Background The Philippines decentralized government health services through devolution to local governments in 1992. Over the years, opinions varied on the impact of devolved governance to decision-making for local health services. The objective of this study was to analyze decision-makers' perspectives on who should be making decisions for local health services and on their preferred structure of health service governance should they be able to change the situation. Methods We employed a mixed methods approach that included an online survey in one region and in-depth interviews with purposively-selected decision-makers in the Philippine health system. Study participants were asked about their perspectives on decision-making in the functions of planning, health financing, resource management, human resources for health, health service delivery, and data management and monitoring. Analysis of survey results through visualization of data on charts was complemented by the themes that emerged from the qualitative analysis of in-depth interviews based on the Framework Method. Results We received 24 online survey responses and interviewed 27 other decision-makers. Survey respondents expressed a preference to shift decision-making away from the local politician in favor of the local health officer in five functions. Most survey participants also preferred re-centralization. Analysis of the interviews suggested that the preferences expressed were likely driven by an expectation that re-centralization would provide a solution to the perceived politicization in decision-making and the reliance of local governments on central support. Conclusions Rather than re-centralize the health system, one policy option for consideration for the Philippines would be to maintain devolution but with a revitalized role for the central level to maintain oversight over local governments and regulate their decision-making for the functions. Decentralization, whether in the Philippines or elsewhere, must not only transfer decision-making responsibility to local levels but also ensure that those granted with the decision space could perform decision-making with adequate capacities and could grasp the importance of health services.